A lithium-ion battery separator modified by high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, and its preparation method and application

By applying a modified coating of high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride on the lithium-ion battery separator, the problems of easy shrinkage and low ion mobility at high temperatures are solved, and higher mechanical strength, thermal stability and ionic conductivity are achieved, improving the safety and performance of the battery.

CN119786879APending Publication Date: 2025-04-08JIANGSU CHAODIAN NEW ENERGY TECH DEV CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411981876.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The separator of traditional lithium-ion battery is prone to shrink in high temperature environments, resulting in short circuits inside the battery and low ion mobility, affecting the charging and discharging efficiency and power density of the battery, limiting the safety performance and cycle stability of the battery.

Method used

The high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride modified lithium-ion battery separator is used to coat the modified coating of fluorine-containing liquid crystal polymer and polyvinylidene fluoride on the surface of the substrate separator to improve the mechanical strength, thermal stability and ionic conductivity of the separator.

Benefits of technology

The modified diaphragm is not prone to heat shrinkage in high temperature environments, which improves the safety and cycle life of the battery, while enhancing the ion mobility and improving the charging and discharging efficiency and power density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786879A_ABST
    Figure CN119786879A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium-ion battery diaphragm modified by high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, and a preparation method and application thereof. The lithium-ion battery diaphragm of the present invention comprises a base diaphragm and a modified coating coated on the surface of the base diaphragm, wherein the modified coating comprises a fluorine-containing liquid crystal polymer and polyvinylidene fluoride. The present invention forms a modified coating by mixing and dissolving the two materials in a suitable solvent, which significantly improves the thermal stability, chemical stability, mechanical strength and ionic conductivity of the diaphragm, thereby improving the safety performance and cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are the main power source for current electronic devices and electric vehicles, and their performance directly affects the endurance and safety of the equipment. As a key component in lithium-ion batteries, the diaphragm has the important tasks of isolating the positive and negative electrodes, preventing short circuits, and allowing lithium ions to pass through. During the battery's charge and discharge process, lithium ions need to migrate between the positive and negative electrodes through the diaphragm, so the ion mobility of the diaphragm has a direct impact on the overall performance of the battery.

[0003] Although traditional polyolefin separators have good mechanical properties and chemical stability, they tend to shrink in high temperature environments, causing internal short circuits in the battery, limiting the battery's safety performance and cycle stability. In addition, traditional separators have low ion mobility and cannot transport ions well, thus affecting the battery's charge and discharge efficiency and power density. In long-term cyclic use, these limitations will gradually reduce the battery's performance and shorten its service life. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, and a preparation method and application thereof.

[0005] The first object of the present invention is to provide a lithium-ion battery separator modified by high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, wherein the lithium-ion battery separator comprises a base separator and a modified coating coated on the surface of the base separator, wherein the modified coating comprises a fluorine-containing liquid crystal polymer and polyvinylidene fluoride.

[0006] In some embodiments of the present invention, the fluorinated liquid crystal polymer is selected from one or more of fluorinated benzoic acid liquid crystal polymers, fluorinated biphenyl liquid crystal polymers, fluorinated diphenyl ether liquid crystal polymers, fluorinated benzophenone liquid crystal polymers, fluorinated diphenyl oxide liquid crystal polymers or fluorinated diphenyl siloxane liquid crystal polymers.

[0007] In some embodiments of the present invention, the amount of polyvinylidene fluoride added is 1-5 wt %.

[0008] In some embodiments of the present invention, the base membrane is selected from one or more of a polyethylene membrane, a polypropylene membrane, a polymer composite membrane and a ceramic coating membrane.

[0009] In some embodiments of the present invention, the base membrane is a microporous membrane with a porosity of 50±5% and a thickness of 10 to 20 microns.

[0010] The second object of the present invention is to provide a method for preparing the lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, comprising the following steps:

[0011] providing a substrate diaphragm;

[0012] A fluorine-containing liquid crystal polymer and polyvinylidene fluoride are selected for mixing and dissolved in an organic solvent to obtain a mixed coating liquid;

[0013] The obtained coating liquid is uniformly coated on the surface of the base diaphragm, and heated and cured to obtain the lithium ion battery diaphragm.

[0014] In some embodiments of the present invention, the organic solvent is selected from one or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0015] In some embodiments of the present invention, the coating thickness of the coating liquid is 1-5 microns.

[0016] In some embodiments of the present invention, the temperature of the heating curing is 30°C-80°C.

[0017] The third object of the present invention is to provide a lithium ion battery, comprising the lithium ion battery separator.

[0018] The above technical solution of the present invention has the following advantages compared with the prior art:

[0019] The present invention uses a mixture of high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride (PVDF) to modify the polyethylene microporous diaphragm. Fluorine-containing liquid crystal polymers are widely used in high-performance applications due to their excellent heat resistance and chemical stability, while PVDF is an ideal binder due to its good adhesion and mechanical properties. The present invention utilizes the orderly arrangement of liquid crystal polymer molecular chains to make the modified diaphragm have higher mechanical strength and toughness, and can withstand greater stress during battery charging and discharging; the present invention improves the heat resistance of the material by utilizing the presence of fluorine-containing groups, so that the diaphragm is not prone to thermal shrinkage or deformation under high temperature conditions, thereby ensuring the safety and life of the battery. The surface energy of the liquid crystal polymer is low, which can effectively prevent excessive adsorption of the electrolyte, while maintaining an appropriate porosity to ensure the smooth conduction of lithium ions. The ordered structure of the liquid crystal polymer helps to evenly distribute the electric field and reduce the inhomogeneity of the local current density, thereby inhibiting the formation of lithium dendrites and extending the cycle life of the battery. At the same time, by mixing and dissolving the two materials in a suitable solvent, a modified coating can be formed, which significantly improves the thermal stability, chemical stability, mechanical strength and ionic conductivity of the diaphragm, thereby improving the safety performance and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0021] Figure 1 It is the cycle curve of the diaphragm prepared in Example 1 and Example 3.

[0022] Figure 2 It is the rate curve of the diaphragm prepared in comparative example 1 and example 3. DETAILED DESCRIPTION

[0023] In order to solve the technical problems pointed out in the background technology, the present invention is implemented by the following scheme:

[0024] The present invention provides a lithium ion battery diaphragm modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride. The lithium ion battery diaphragm comprises a base diaphragm and a modified coating coated on the surface of the base diaphragm. The modified coating comprises a fluorine-containing liquid crystal polymer and polyvinylidene fluoride.

[0025] In some embodiments of the present invention, the fluorinated liquid crystal polymer is selected from one or more of fluorinated benzoic acid liquid crystal polymers, fluorinated biphenyl liquid crystal polymers, fluorinated diphenyl ether liquid crystal polymers, fluorinated benzophenone liquid crystal polymers, fluorinated diphenyl oxide liquid crystal polymers or fluorinated diphenyl siloxane liquid crystal polymers.

[0026] In some embodiments of the present invention, the addition amount of the polyvinylidene fluoride is 1-5wt%, illustratively, it can be 1, 2, 3, 4, 5wt%, etc., or any interval value between any two values.

[0027] In some embodiments of the present invention, the base membrane is selected from one or more of a polyethylene membrane, a polypropylene membrane, a polymer composite membrane and a ceramic coating membrane.

[0028] In some embodiments of the present invention, the base membrane is a microporous membrane with a porosity of 50±5% and a thickness of 10 to 20 microns. For example, it can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 20 microns, etc., or any interval value between any two values.

[0029] The second object of the present invention is to provide a method for preparing the lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, comprising the following steps:

[0030] providing a substrate diaphragm;

[0031] A fluorine-containing liquid crystal polymer and polyvinylidene fluoride are selected for mixing and dissolved in an organic solvent to obtain a mixed coating liquid;

[0032] The obtained coating liquid is uniformly coated on the surface of the base diaphragm, and heated and cured to obtain the lithium ion battery diaphragm.

[0033] In some embodiments of the present invention, the organic solvent is selected from one or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0034] In some embodiments of the present invention, the coating thickness of the coating liquid is 1-5 microns, and illustratively, it can be 1, 2, 3, 4, 5 microns, etc., or any interval value between any two values.

[0035] In some embodiments of the present invention, the temperature of the heating and curing is 30°C-80°C, and illustratively, it can be 30, 40, 50, 60, 70, 80°C, etc., or any interval value between any two values.

[0036] The third object of the present invention is to provide a lithium ion battery, comprising the lithium ion battery separator.

[0037] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0038] Embodiment 1:

[0039] This embodiment provides a method for preparing a lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, which specifically comprises the following steps:

[0040] (1) Base membrane: A commercially available polyethylene microporous membrane was selected with a porosity of 50% and a thickness of 15 μm.

[0041] (2) Coating liquid: A fluorinated benzoic acid liquid crystal polymer, specifically 4-(2-methylbutyloxy)phenyl 4-(4-fluorophenyl)benzoate, and PVDF were mixed at a mass ratio of 95:5 and dissolved in NMP to obtain a coating liquid of the fluorinated benzoic acid liquid crystal polymer.

[0042] (3) Coating: Use a scraper to evenly coat the coating liquid obtained in step (2) on the base membrane to a coating thickness of 2 μm.

[0043] (4) Curing: drying the separator coated with the fluorinated benzoic acid liquid crystal polymer obtained in step (3) at 60° C. for 60 minutes to obtain the lithium ion battery separator.

[0044] Performance test: The modified diaphragm exhibits excellent thermal stability and chemical stability.

[0045] Embodiment 2:

[0046] This embodiment provides a method for preparing a lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, which specifically comprises the following steps:

[0047] (1) Base membrane: A commercially available polyethylene microporous membrane was selected with a porosity of 48% and a thickness of 18 μm.

[0048] (2) Coating liquid: A fluorinated biphenyl liquid crystal polymer, specifically 4-fluoro-4'-hydroxybiphenyl-4-carboxylic acid, is selected and mixed with PVDF at a mass ratio of 90:10, and dissolved in DMF to obtain a coating liquid of the fluorinated biphenyl liquid crystal polymer.

[0049] (3) Coating: Use a roller coater to evenly coat the coating liquid obtained in step (2) on the base diaphragm, with a coating thickness of 3 μm.

[0050] (4) Curing: drying the diaphragm coated with the fluorinated biphenyl liquid crystal polymer obtained in step (3) at 70° C. for 50 minutes to obtain the lithium ion battery diaphragm.

[0051] Performance test: The modified membrane has higher mechanical strength and ionic conductivity.

[0052] Embodiment 3:

[0053] This embodiment provides a method for preparing a lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, which specifically comprises the following steps:

[0054] (1) Base membrane: A commercially available polyethylene microporous membrane was selected with a porosity of 52% and a thickness of 12 μm.

[0055] (2) Coating liquid: A fluorinated diphenyl ether liquid crystal polymer, specifically 4-(4-fluorophenyl)benzoic acid 4-(2-ethylhexyloxy)phenyl ester, and PVDF were mixed at a mass ratio of 98:2 and dissolved in DMSO to obtain a coating liquid containing a fluorinated diphenyl ether liquid crystal polymer.

[0056] (3) Coating: Use an airless sprayer to evenly coat the coating liquid obtained in step (2) on the base diaphragm, with a coating thickness of 4 μm.

[0057] (4) Curing: The separator coated with the fluorinated diphenyl ether liquid crystal polymer obtained in step (3) is dried at 80° C. for 45 minutes to obtain the lithium ion battery separator.

[0058] Performance test: The modified diaphragm exhibits extremely low thermal shrinkage in high temperature environment.

[0059] Embodiment 4:

[0060] This embodiment provides a method for preparing a lithium ion battery separator modified by high temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride, which specifically comprises the following steps:

[0061] (1) Base membrane: A commercially available polyethylene microporous membrane was selected with a porosity of 45% and a thickness of 20 μm.

[0062] (2) Coating liquid: A fluorinated benzophenone liquid crystal polymer, specifically 4-(4-fluorophenyl)benzoic acid p-fluorophenyl ester, is selected and mixed with PVDF in a mass ratio of 92:8, and dissolved in a mixed solvent of NMP and DMF (the volume ratio of the two is 1:1) to obtain a coating liquid of the fluorinated benzophenone liquid crystal polymer.

[0063] (3) Coating: Use a scraper to evenly coat the coating liquid obtained in step (2) on the base membrane, with a coating thickness of 1 μm.

[0064] (4) Curing: The diaphragm coated with the fluorinated benzophenone-based liquid crystal polymer obtained in step (3) was dried at 60° C. for 60 minutes.

[0065] Performance Testing:

[0066] The modified diaphragm has good chemical stability and mechanical strength.

[0067] Comparative Example 1

[0068] Conventional PP films in the prior art have a porosity of 52% and a thickness of 12 microns.

[0069] Performance Testing

[0070] 1. The performance of the diaphragms obtained in the examples and comparative examples was tested as follows:

[0071] (1) Adhesion force: The specific detection method is as follows: Compound the diaphragm and the electrode material together. Use a universal material testing machine to peel the diaphragm from the electrode at a constant speed of 50 mm / min. Record the force required during the peeling process and calculate the average value. The experimental results are shown in Table 1.

[0072] (2) Thermal shrinkage rate, the specific detection method is as follows:

[0073] S1. Cut a diaphragm of a certain specification and draw a gauge line in the middle of the diaphragm.

[0074] S2. Clamp one end of the diaphragm on the fixing fixture of the test device.

[0075] S3. Pass the clamped diaphragm smoothly around the test bench and clamp the other end on the movable fixture.

[0076] S4. Hang a certain weight on the movable fixture, and fix the movable fixture after the whole system is stable. Place the whole test system in an oven and bake at 130℃ for 1h.

[0077] S5. Take out the test system, remove the diaphragm, and measure the distance L1 between the gauge lines (length is 200 mm). The experimental results are shown in Table 1.

[0078] S6. Repeat the test 5 times and take the average value of the test results. Calculate the thermal shrinkage rate, thermal shrinkage rate = (200-L1) / 200×100%.

[0079] (3) Air permeability: the specific testing method is as follows:

[0080] S1. Using the air permeability measurement process, the lithium battery diaphragm air permeability test process includes: fixing the lithium battery diaphragm, applying air pressure on one side of the diaphragm, measuring the air pressure drop and the time used, and detecting the air permeability of the diaphragm.

[0081] S2. When the lithium battery separator is fixed, a certain pressure is applied to one side of the separator. Due to the micropores on the separator, the pressure will gradually decrease until it is equal to the atmospheric pressure.

[0082] S3. By comparing the time taken for the pressure to drop from the initial pressure to the final pressure, the air permeability of the diaphragm can be determined.

[0083] S4. By comparing the pressure drop time of different diaphragms, their air permeability performance can be compared. The shorter the pressure drop time, the better the air permeability.

[0084] S5. The whole measurement process is simple and convenient, and the data information can directly reflect the air permeability of the membrane, which has obvious applicability. The experimental results are shown in Table 1.

[0085] (4) Oxygen index: The specific detection method is as follows: Place the diaphragm sample in the test equipment and set the test parameters. Ignite the sample and record the burning time and length. During the test, adjust the gas mixing and flow control device so that the oxygen concentration in the mixed gas is the oxygen concentration determined at the beginning, and flow through the combustion tube at a speed of (40±10) mm / s to wash the combustion tube for at least 30 seconds. After the sample is ignited, start timing immediately to observe the burning length and combustion behavior of the sample. If the combustion stops but spontaneously reignites within 1 second, continue to observe and time. Adopt the specific condition of "a small amount of sample up-down method" and use any step length as the change amount to test a group of samples according to the above method. If the combustion behavior of the previous sample is an "X" reaction, reduce the oxygen concentration; if the combustion behavior of the previous sample is an "O" reaction, increase the oxygen concentration. Use any appropriate step length and repeat the test until the difference between the secondary oxygen concentrations expressed as volume fraction is no more than 1.0%, and one is an "O" reaction and the other is an "X" reaction. The "O" reaction in this group of oxygen concentrations is recorded as the initial oxygen concentration. Through the above steps, the oxygen index of the diaphragm can be accurately detected, thereby evaluating its combustion characteristics under oxygen conditions. The experimental results are shown in Table 1.

[0086] Table 1

[0087]

[0088] 2. Electrochemical performance test of the membranes obtained in Examples 1 to 4 and the comparative example

[0089] (1) Cycle curves of Example 3 and Comparative Example 1: Experimental results are shown in Figure 1 .

[0090] (2) Rate characteristic curves of Example 3 and Comparative Example 1:

[0091] The positive electrode of the battery is NCM811, the negative electrode is lithium metal, the electrolyte is 1M LiPF6EC / EMC=3:7, and a button cell is prepared according to Example 3 for electrochemical performance testing: the battery is charged to 4.5V and discharged to 3V, with a charge and discharge of 0.5C. The experimental results are shown in Figure 2 ,from Figure 2 The charge and discharge curve results shown show that the battery prepared in Example 3 has a higher specific capacity and better rate characteristics.

[0092] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A lithium-ion battery separator modified by high-temperature fluorinated liquid crystal polymer and polyvinylidene fluoride, characterized in that: The lithium-ion battery separator comprises a base separator and a modified coating coated on the surface of the base separator, wherein the modified coating comprises a fluorine-containing liquid crystal polymer and polyvinylidene fluoride.

2. The lithium-ion battery separator modified by high-temperature fluorinated liquid crystal polymer and polyvinylidene fluoride according to claim 1, characterized in that: The fluorine-containing liquid crystal polymer is selected from one or more of fluorine-containing benzoic acid liquid crystal polymers, fluorine-containing biphenyl liquid crystal polymers, fluorine-containing diphenyl ether liquid crystal polymers, fluorine-containing benzophenone liquid crystal polymers, fluorine-containing diphenyl oxide liquid crystal polymers or fluorine-containing diphenylsiloxane liquid crystal polymers.

3. The lithium-ion battery separator modified by high-temperature fluorinated liquid crystal polymer and polyvinylidene fluoride according to claim 1, characterized in that: The added amount of the polyvinylidene fluoride is 1-5wt%.

4. The lithium-ion battery separator modified by high-temperature fluorinated liquid crystal polymer and polyvinylidene fluoride according to claim 1, characterized in that: The base diaphragm is selected from one or more of a polyethylene diaphragm, a polypropylene diaphragm, a polymer composite diaphragm and a ceramic coating diaphragm.

5. The lithium-ion battery separator modified by high-temperature fluorinated liquid crystal polymer and polyvinylidene fluoride according to claim 1, characterized in that: The base membrane is a microporous membrane with a porosity of 50±5% and a thickness of 10 to 20 microns.

6. The method for preparing a lithium-ion battery separator modified by high-temperature fluorine-containing liquid crystal polymer and polyvinylidene fluoride according to any one of claims 1 to 5, characterized in that: The following steps are involved: providing a substrate diaphragm; A fluorine-containing liquid crystal polymer and polyvinylidene fluoride are selected for mixing and dissolved in an organic solvent to obtain a mixed coating liquid; The obtained coating liquid is uniformly coated on the surface of the base diaphragm, and heated and cured to obtain the lithium ion battery diaphragm.

7. The preparation method according to claim 6, characterized in that: The organic solvent is selected from one or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

8. The preparation method according to claim 6, characterized in that: The coating thickness of the coating liquid is 1-5 microns.

9. The preparation method according to claim 6, characterized in that: The temperature of the heating curing is 30°C-80°C.

10. A lithium ion battery, characterized in that: The invention comprises the lithium ion battery separator according to any one of claims 1 to 5.

Citation Information

Cited By

  • Three-layer composite diaphragm and preparation method thereof

    CN120565989B

  • Preparation method of three-layer composite diaphragm

    CN121688334A

  • Sand grain-electrolyte interlayer quasi-solid-state lithium ion battery and preparation method thereof

    CN121839822A

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN122051403A

  • Battery cell, method for producing the same, battery device, electric device, and energy storage device

    CN122051403B